ANALISIS KESALAHAN GRAMATIKA MAHASISWA LP3I POLITEKNIK JAKARTA PADA MATA KULIAH BUSINESS ENGLISH CORRESPONDENCE - Andi Setiawan (POLITEKNIK LP3I JAKARTA, 2020)
The ability to speak English both verbally and in writtenly for LP3I students is an important asset to be able to compete in the MEA era. However, for them English is not an easy subject to study. This is evident from the results of this study. Business English Correspondence is a course that provides expertise to students in conducting business correspondence in English well and correctly. The purpose of this paper is to find out the mistakes of English grammar in conducting business correspondence both conventional and online. Through the principles of error analysis, it can be seen various types of grammatical errors that are not in accordance with English grammar. There are two forms of errors that are generally distributed by students, namely Interlingual Error and Intralingual Error. The tables and graphs shown in this study describe twelve types of grammatical errors of students who have been classified. Strategic steps to evaluate the teaching methods of this course can be done afterwards.Key words: Error analysis, English Grammar. Business English Correspondence.